Karakterisasi Struktur dan Morfologi Membran Polietersulfon dengan Penambahan Variasi Katalis Organik Titanium Dioksida - Khuluqa, M Afif Al Ahsan; Mardwita, Mardwita; Yuliawati, Erna (Penerbit Goodwood, 2024)
This study aims to synthesize and characterize ultrafiltration membranes based on polyethersulfone (PES) with the incorporation of titanium dioxide (TiO?) as an organic catalyst at varying concentrations (0%, 1%, and 2%). The goal is to evaluate the impact of TiO? addition on the structural and morphological properties of PES membranes to improve water treatment performance. Research/methodology: Membranes were fabricated using the phase inversion technique, employing N,N-dimethylacetamide (DMAc) as the solvent and polyvinylpyrrolidone (PVP) as the pore-forming additive. Characterization techniques included Fourier-transform infrared spectroscopy (FTIR) for functional group identification, scanning electron microscopy (SEM) and atomic force microscopy (AFM) for morphological analysis, contact angle measurement for hydrophilicity, porosity testing, and pure water flux evaluation. Results: The addition of TiO? improved the hydrophilicity of PES membranes, reducing the contact angle from 68.2° to 53.7°, and increased porosity from 48.78% to 67.75%. Morphological analysis showed enhanced pore distribution and surface structure. The membrane with 2% TiO? achieved the highest water flux of 5.77 L/m²·h. Although this value is below the typical ultrafiltration standard (10–50 L/m²·h), the improvements indicate the potential of TiO? to enhance membrane performance. Conclusions: Incorporating TiO? into PES membranes significantly enhanced their hydrophilicity, porosity, and structural uniformity. The optimal performance was observed at a 2% TiO? concentration. Limitations: The study is limited by the non-uniform dispersion of TiO? particles and was conducted under laboratory-scale conditions without real-world application testing. Contribution: This research provides insight into the role of TiO? in improving PES membrane characteristics and serves as a practical reference for developing advanced ultrafiltration membranes for water treatment applications.